Pengaruh Perbedaan Feeding Time Hijauan-Konsentrat Berdasarkan Day in Milk Terhadap Produksi dan Berat Jenis Susu Sapi PFH (Peranakan Friess Holland) - Syaiful Arifin; Muhammad Farid Wajdi; Inggit Kentjonowaty (International Journal of Animal Science, 2021)
The influence of different feeding times forage and concentrate based on day in milk on the production and density of PFH (Friess Holland's) cow's milk. The materials used were PFH cattle aged 3 years, 2nd lactation period, elephant grass (Penicetum purpureum CV. Hamill), odot grass (Penicetum purpureum CV. Mott), Dairy cow concentrate A20. The experimental method was randomized block design (RBD). Then proceed with the Least Significant Difference Test (LSD) if the results have a real or very real effect. Feeding time was divided into P1 = Giving concentrate then giving forage after 1 hour, P2 = giving forage then giving concentrate after 1 hour, P3 = giving forage and concentrate simultaneously. The group division in this study was divided into 3 groups based on the month of lactation where K1 = 3-4 months, K2 = 5-6 months, and K3 = 7 months. The results of treatment based on data analysis based on analysis of variety showed a significant effect (P <0,05) between forage-concentrate feeding time based on day in milk on milk production. Meanwhile, the difference in forage-concentrate feeding time based on day in milk had no significant effect on specific gravity (P> 0,05). The average value of milk production from each treatment for 10 days P1 = 759.17a liter, P2 = 724a liter, P3 = 833.50b liter. The average value of milk production from each group for 10 days K1 = 1,012 liters, K2 = 820 liters, K3 = 506 liters from 21 PFH cows. The average density value of milk from each treatment for 10 days P1 = 1,0237 gr / ml, P2 = 1,0237 gr / ml, P3 = 1,0243 gr / ml. The average density value of milk from each group for 10 days from 21 PFH K1, K2 and K3 cows showed the same value, namely 1.024 g / ml. It was concluded that there was a significant difference in feeding time forage and concentrate on milk production. With the best treatment P3 which is the provision of forage and concentrate simultaneously.